Patient-Centered Research: Ignorance in the Face of Death: Patients' Knowledge of Options at the End of Life - Silveira, MJ (Blackwell Science Inc, 2000)
PURPOSE: That patients correctly understand their legal options regarding end-of-life care is critical, especially given recent legislation promoting use of advance directives (Patient Self Determination Act) and legalizing assisted suicide (Oregon Death with Dignity Act). We know little, however, about outpatients' understanding of these matters. We therefore sought to estimate the percentage of outpatients informed about refusal and withdrawal of life saving treatments, physician-assisted suicide, active euthanasia, and double effect. In addition, we tested whether personal experience of illness or the care of dying loved ones was associated with knowledge about end-of-life care. METHODS: Using a pre-tested knowledge questionnaire, we cross-sectionally surveyed patients from 1 internal medicine, university-based clinic and 3 community-based, university-affiliated, mixed internal medicine and family practice clinics in Oregon. English-speaking, adult outpatients were invited to participate in the study as they checked in consecutively for primary care. After calculating the percentage of correct responses regarding the four topic areas, we identified demographic factors associated with being knowledgeable (defined as scoring above the median for the survey population) using Chi-square test of proportions. We then tested the adjusted association between personal experiences and knowledge using logistic regression modeling. RESULTS: Of the 1,000 outpatients invited to participate, 728 consented and completed the questionnaire. 65% of respondents answered correctly for refusal of treatment, 46% for withdrawal of treatment, 23% for assisted suicide, 32% for active euthanasia, and 69% for double effect. 62% of respondents did not distinguish between assisted suicide and euthanasia. With adjustment for other covariates, knowledge was significantly associated with being white (OR 3.11, 95% CI 1.39–6.97), having at least a college degree (OR 2.12, 95% CI 1.15–3.94), and having been a proxy for healthcare decisions (OR 1.69, 95% CI 1.13–2.52). Personal experience with illness (OR 1.02, 95% CI 0.65–1.60), death or illness of a loved one (OR 1.56, CI 95% 0.93–2.61), and authoring an advance directive (OR 1.31, 95% CI 0.88–1.94) were not associated with better knowledge. CONCLUSION: A significant proportion of outpatients at university-affiliated clinics in Oregon appear to misunderstand options in end-of-life care. Greater public knowledge about end-of-life care, especially for patients facing terminal illness and considering assisted suicide, is needed.